2019
DOI: 10.1002/kjm2.12123
|View full text |Cite
|
Sign up to set email alerts
|

Rhein lysinate improves motor function in rats with spinal cord injury via inhibiting p38 MAPK pathway

Abstract: The current study aims to investigate the effect of rhein lysinate (RHL) on neuromotor function in rats with spinal cord injury (SCI) and to explore the underlying mechanism. A total of 63 adult male SD rats were randomly divided into the sham group, SCI group and RHL group (SCI‐RHL group), with 21 rats in each group. Basso Beattie Bresnahan (BBB) scoring and the inclined plate test were used to evaluate the changes in motor function after SCI. Then, superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…According to previous research, rhein can sensitize human pancreatic cancer cells to EGFR inhibitors by inhibiting the STAT3 pathway (Yang et al, 2019). In addition, Hao et al found that rhein improved motor function in rats with spinal cord injury by inhibiting the P38/MAPK pathway (Hao et al, 2019). Ma et al showed that rhein can affect the malignant phenotype of renal cancer by inhibiting MAPK/NF-κB signaling (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, rhein can sensitize human pancreatic cancer cells to EGFR inhibitors by inhibiting the STAT3 pathway (Yang et al, 2019). In addition, Hao et al found that rhein improved motor function in rats with spinal cord injury by inhibiting the P38/MAPK pathway (Hao et al, 2019). Ma et al showed that rhein can affect the malignant phenotype of renal cancer by inhibiting MAPK/NF-κB signaling (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…3.8. Mt activates the MAPK signaling pathway in vitro and in vivo JNK, Erk1/2, and p38 MAPK, three important members of mitogen-activated protein kinase (MAPK) family, are closely associated with apoptosis and oxidative stress [33,34]. To determine whether Mt triggers MAPK signaling, the expression and phosphorylation of MAPK signaling proteins was respectively detected by Western blot and immuno uorescence staining, both in vitro and in vivo.…”
Section: Nac Pretreatment Attenuated Mt-induced Cytotoxicitymentioning
confidence: 99%